Experimental analysis of ¹³CO₂ infrared stimulated - Chabbi, H.; Dahoo, P.R.; Dubost, H.; Gauthier-Roy, B.; Vasserot, A.-M.; Abouaf-Marguin, L. (Физика низких температур, 2000)
Vibrational stimulated emissions of CO₂ trapped in low temperature argon matrices have been found experimentally not only in the 16 mm region (v₂ manifold) but also at 10 mm (v₃ - v₁ transition) in the double trapping site of concentrated samples. A detailed experimental description of these emissions is reported, including spectral analysis, time-resolved studies, laser energy dependence, and concentration and temperature effects. The characteristics of the emissions are discussed, giving some insight into the nonradiative intramolecular V–V transfers from the laser excited level v₃=1 towards the v₂ manifold, and inside this manifold.